La contribución de la educación al desarrollo social - Quintana Cabanas, José María (2000)
Education contributes to economic development. However, the ideal development is the Human one. Education is one of the main factors involved in Human Development. The Social Development of the countries has to improve their social, political and mental structures. Strategies to improve social development include Birth Control, Family Assistance, Women Promotion, Social Equality, and Human Rights promotion. Ali this may be achieved by Education, through democratic ideas, innovation, and individual development of people and social groups.